Postharvest quality, technologies, and strategies to reduce losses along the supply chain of banana: A review. (April 2023) - Al-Dairi, Mai; Pathare, Pankaj B.; Al-Yahyai, Rashid; Jayasuriya, Hemanatha; Al-Attabi, Zahir
Abstract: Background: Banana fruit is a popular crop in global agriculture production and trade. Bananas are delicate fresh produce where external factors can highly affect their quality resulting in high losses during the postharvest supply chain. Scope and approach: This paper describes the most common nutritional, chemical, physical, and physiological quality attributes of the banana fruit. It also discusses the practiced technologies that are employed in the supply chain of bananas and their influence on banana fruit characteristics. Postharvest technologies play a crucial role in preserving fruits. Before implementing appropriate postharvest technology, it is essential to understand the quality changes in banana fruit during the ripening process. Key findings and conclusions: Various technologies are being used like storage, artificial ripening, packaging, handling, and transportation for bananas within the supply chain. The review can increase awareness and knowledge by selecting and implementing suitable postharvest techniques to enhance postharvest shelf-life and retain the nutritional and marketable quality of this important fruit. Relevant recent studies on banana packaging are highlighted and some current non-destructive image processing techniques applied to bananas are described. Ultimately, this review suggests strategies to reduce postharvest losses in the physical, chemical, and nutritional quality of banana fruit and provides future research trends to achieve fruit safety, security, and quality. Highlights: Banana is one of the most popular fruit and has a high nutritional content. The main postharvest operations in the postharvest supply chain are discussed. The effect of storage, transportation, and packaging on bananas was reviewed. Using image processing for damage detection on banana fruit was described. Different strategies to reduce postharvest losses in bananas were suggested.